The course delivery process in LMS - Kulvietienė, Regina; Stankevič, Jelena; Šileikienė, Irma (Lietuvos matematikos rinkinys, 2005)
Learning management systems (LMS) characterized by component architecture base on learning technology standards. Therefore, e-learning content can be developed by using different standalone authoring tools or repurposed from other applications content. SCORM and AICC are most popular standards. Requirements for SCORM e-learning components can be stated as: durability, accessibility, interoperability and reusability, therefore content standards include places for learning object metadata. Package includes content, metadata about the content, metadata about the course, and the course structure.
Keywords: e-learning system; e-learning content; SCORM; authoring tool